Influence of substrates and in vitro preconditioning treatments on ex vitro acclimatization of Arachis retusa - Pacheco, Georgia; Gagliardi, Rachel Fátima; Cogliatti, Mariana Buturini; Manhães, Harlen Barreira; Carneiro, Leonardo Alves; Valls, José Francisco Montenegro; Mansur, Elisabeth (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the influence of substrate and preconditioning treatments on the acclimatization of in vitro plants of Arachis retusa. Plants were transferred to Plantmax or sand, and fertilized with Hoagland’s nutrient solution. Plants maintained in sand, with or without fertilizer, showed the highest survival rates. In order to evaluate the influence of in vitro preconditioning treatments, stem segments were cultured on MS medium supplemented with different sucrose concentrations. The highest survival and developmental rates were observed in plants from two accessions cultured on MS supplemented with 1.5% and 3% sucrose. Flowering and fruit production were observed after five months.